Agencies in European Banking A Critical Perspective - Božina Beroš, Marta (Palgrave Macmillan Studies in Banking and Financial Institutions,, 2018)
This book studies relationship dynamics between National Competent Authorities (NCAs) within two agencies governing the European banking sector: the European Banking Authority and the Single Resolution Board. The analysis centres on NCAs policy preferences and the variety thereof, particularly in the context of banking market fragmentation (Euro area vs. non-Euro area countries/banking union "ins" and "outs"). The focus is not so much on the motivations of these preferences, but on the processes and mechanisms that help reach NCAs consensus on prudential matters. Through an interdisciplinary approach rooted in legal analysis and political economy, the book shows how national actors inform decision-making within European agencies in banking, and whether-and how-the reality of differentiated integration within the internal banking market challenges policy creation.